2001
DOI: 10.1101/gad.906601
|View full text |Cite
|
Sign up to set email alerts
|

Binding of c-Myc to chromatin mediates mitogen-induced acetylation of histone H4 and gene activation

Abstract: The Myc protein binds DNA and activates transcription by mechanisms that are still unclear. We used chromatin immunoprecipitation (ChIP) to evaluate Myc-dependent changes in histone acetylation at seven target loci. Upon serum stimulation of Rat1 fibroblasts, Myc associated with chromatin, histone H4 became locally hyperacetylated, and gene expression was induced. These responses were lost or severely impaired in Myc-deficient cells, but were restored by adenoviral delivery of Myc simultaneous with mitogenic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
462
2
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 455 publications
(485 citation statements)
references
References 60 publications
(107 reference statements)
18
462
2
3
Order By: Relevance
“…Rather, the results would suggest that the initial Myc interaction creates a state that facilitates the subsequent E2F1 interaction, possibly through a chromatin modification process. As such, we have demonstrated through ChIP assays that knockdown of Myc expression reduced acetylation on histone H4, consistent with previous work demonstrating a role for Myc in affecting H4 acetylation (Frank et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Rather, the results would suggest that the initial Myc interaction creates a state that facilitates the subsequent E2F1 interaction, possibly through a chromatin modification process. As such, we have demonstrated through ChIP assays that knockdown of Myc expression reduced acetylation on histone H4, consistent with previous work demonstrating a role for Myc in affecting H4 acetylation (Frank et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…We propose that the requirement of Myc for activation of E2F genes may be to provide a 'licensing event', to ensure that the E2F genes are only activated when Myc activity has previously accumulated. Consistent with this speculation, recent studies have also indicated that Myc may act as a 'permissive' factor to allow other signals to activate target promoters (Frank et al, 2001). By so doing in the context of E2F gene promoter regulation and cell-cycle progression, cells would then only enter S phase when all of the necessary components for cell growth, encoded by the other myriad of genes regulated by Myc, have properly accumulated.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…rMTA1 and rODC promoters possess 10 and four E-boxes, respectively (Figure 6a). In growing K2 cells, c-Myc, rSGF29 and acetylated histone H3 were detected in the promoter regions, whereas in the E-boxless promoter of rat acetylcholine receptor (ACHR) gene (Frank et al, 2001), these proteins were hardly detected ( Figure 6b). In quiescent K2 cells the binding levels of these proteins were reduced.…”
Section: Resultsmentioning
confidence: 99%